Novos arranjos urbanos e regionais dos movimentos migratórios no município de Cachoeiro de Itapemirim (ES) - Santos, Yago Oliveira dos (2023)
Internal migrations have a vast literature in the Brazilian academy, investigating, analyzing, problematizing and seeking to understand the reasons, causes, origins, destinations, their modalities and several other issues that involve this theme. It is from this set of discussion of internal migrations that this work was developed. Thus, this work aims to seek to understand the conditions that understand and discuss the departure from a space of migratory gain to a space of migratory loss that involves the municipality of Cachoeiro de Itapemirim in the face of economic changes. Combined with this, there is the importance of understanding this municipality as a medium, polarizing and central city within a region. To achieve this objective, this work used a quantitative analysis based on census data from 1991, 2000 and 2010 to analyze migratory flows and the population characteristics of these migrants, also including in the discussion of the migratory profile of entry and exit. In order to understand the economic issues, work data from the RAIS and the census were used. Also together with these, an analysis of the public and private investments of the Jones dos Santos Neves Institute is also carried out. Therefore, this work begins by discussing the main debates within the literature that surrounds this work, and also bringing the relationships that can be established between urban, population and regional issues. Soon after, a historical analysis is made of the municipality of Cachoeiro de Itapemirim throughout the twentieth century within the urban network of Espírito Santo and the migratory movements inserted in these contexts. Finally, the economic and migratory constraints are analyzed to discuss the new contexts of migratory loss in the municipality of Cachoeiro. The results demonstrate that the status of loser municipality of migrants also follow the changes in the urban network of Espírito Santo in terms of economic transformations. It is seen that Cachoeiro de Itapemirim, although it was an important regional centrality throughout the first decades of the twentieth century, the concentration of economic investments on the coast of Espírito Santo, mainly due to oil and gas, ends up also directing the new migratory movements, and at the same time municipalities that do not directly participate in this productive network, such as the municipality in this research, end up showing economic stagnation.